2011
DOI: 10.1002/bjs.7459
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative course and clinical significance of biochemical blood tests following hepatic resection

Abstract: Biochemical data may help to recognize surgery-related complications early during the postoperative course, and serve as the basis for the definition of complications after hepatic resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
55
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(62 citation statements)
references
References 32 publications
5
55
0
Order By: Relevance
“…The 90-day mortality (4.6%) and morbidity (14.7%) rate are similar to published series [4, 18, 38], although other series have included minor (Grade I and II) complications [3941]. Composite outcomes similar to the one used in this study have been used previously in studies evaluating outcomes following gastrointestinal surgery [42, 43].…”
Section: Discussionsupporting
confidence: 71%
“…The 90-day mortality (4.6%) and morbidity (14.7%) rate are similar to published series [4, 18, 38], although other series have included minor (Grade I and II) complications [3941]. Composite outcomes similar to the one used in this study have been used previously in studies evaluating outcomes following gastrointestinal surgery [42, 43].…”
Section: Discussionsupporting
confidence: 71%
“…Grade A PHLF was diagnosed in 5 patients (8%), grade B in 47 patients (72%) and grade C in 13 patients (20%). The perioperative mortality of patients with PHLF grade A, B, and C was 0, 12 and 54%, respectively [36]. …”
Section: Definition Of Phlfmentioning
confidence: 99%
“…13 More recently, biochemical blood tests have been proposed as not only an accurate means to predict mortality, but perhaps even morbidity. 16 Reiss-felder and colleagues reported that biochemical data can help to recognize patients more likely to have a surgery-related complication during the postoperative course. 16 …”
mentioning
confidence: 99%
“…16 Reiss-felder and colleagues reported that biochemical data can help to recognize patients more likely to have a surgery-related complication during the postoperative course. 16 …”
mentioning
confidence: 99%
See 1 more Smart Citation